The effect of fertilization with sulphur on uptake and utilization of nitrogen by winter wheat - Winiarski, Ryszard; Ochal, Piotr (Polish Journal of Agronomy, 2021)
This paper presents the results of a four-year field study on the effect of sulphur fertilization on nitrogen uptake and its utilization efficiency by winter wheat. A two-factor field ex- periment was carried out over 1999–2002 in a randomized blocks design. The first factor was fertilization with sulphur (in the form of sulphate) in doses of 0 and 60 kg ha-1, while the second fac- tor – nitrogen fertilization (in the form of ammonium nitrate) in doses of 0, 30, 60, 90, 120 and 150 kg N ha-1. Nitrogen was ap- plied in doses of 30 kg N ha-1, at two-week intervals after the start of growing season. The research showed that sulphur fertiliza- tion increased on average the nitrogen uptake by wheat by 3.5%. The efficiency index of nitrogen fertilization of wheat had higher values after application of fertilizers containing sulphur with a tendency to decrease as the dose N increased. Sulphur fertiliza- tion increased the agronomic efficiency of nitrogen in the range of low doses from 30 to 90 kg N ha-1.